Prognostic Factors Predict Oncological Outcome in Older Patients With Head and Neck Cancer Undergoing Chemoradiation Treatment - Stromberger, Carmen; Yedikat, Berna; Coordes, Annekatrin; Tinhofer, Ingeborg; Kalinauskaite, Goda; Budach, Volker; Zschaeck, Sebastian; Raguse, Jan-Dirk; Kofla, Grzegorz; Heiland, Max; Stsefanenka, Aksana; Beck-Broichsitter, Benedicta; et al. (Frontiers in Oncology, 2021)
Purpose: Older patients with head and neck cancer (HNC) represent a challenging group, as frailty and comorbidities need to be considered. This study aimed to evaluate the efficacy and side effects of curative and palliative (chemo) radiation ([C]RT) with regard to basic geriatric screening in older patients. Methods: This study included HNC patients aged ≥ 70 years who were treated with curative or palliative (C)RT. Clinicopathological data including Charlson Comorbidity Index (CCI), Karnofsky performance status (KPS), and treatment data were analyzed as predictors of overall survival (OS). Results: A total of 271 patients (median age, 74 years) were enrolled. The majority had UICC stage III/IV (90%) and underwent curative treatment (85.2%). A total of 144 (53.1%) patients received definitive and 87 (32.1%) had adjuvant (C)RT. Overall, 40 patients (14.8%) received palliative (C)RT. Median follow-up duration (curative setting) was 87 months, and the 2- and 5-year OS rates were 57.8% and 35.9%, respectively. Median OS was significantly different for age ≤ 75 vs. > 75 years, CCI < 6 vs. ≥ 6, KPS ≥ 70% vs. < 70%, Tx/T1/T2 vs. T3/T4, and adjuvant vs. definitive (C)RT, respectively. Age 70–75 years (p = 0.004), fewer comorbidities when CCI < 6 (p = 0.014), good KPS ≥ 70% (p = 0.001), and adjuvant (C)RT (p = 0.008) independently predicted longer survival. Palliative RT resulted in a median OS of 4 months. Conclusion: Older age, lower KPS, higher CCI, and definitive (C)RT are indicators of worse survival in older patients with HNC treated curatively. Without a comprehensive geriatric assessment in patients aged > 75 years, the KPS and CCI can be useful tools to account for "fitness, vulnerability or frailty" to help in treatment decision-making.